Convalescent plasma therapy prevents acute respiratory distress syndrome in patients with SARS-CoV-2 virus disease - Macías Abraham, Consuelo; Porto González, Delia Esther; Legrá Ayala, Ariel; Forrellat Barrios, Mariela; Lam Díaz, Rosa María; Cordoví Rodríguez, Damisela; Ortega León, Lillebit; Ballester Planes, Laura; García Domínguez, Kalina; González Maldonado, Zuleidi; FrómetaTolón, Zunilda; Rodríguez Hernández, Milaidys; et al. (Revista Cubana de Hematología, Inmunología y Hemoterapia, 2020)
BACKGROUND: SARS-CoV-2 disease 2019 is a pandemic with no specific therapeutic agents and substantial mortality. The success of convalescent plasma therapy is based on the transfused plasma had high concentrations of anti-SARS-CoV-2 antibodies, and on the safe preparation of serum to eliminate potential risk factors, such as the transmission of viruses via transfusion. STUDY DESIGN AND METHODS: Five patients laboratory confirmed COVID-19, diagnosed using reverse transcriptase–polymerase chain reaction (RT-PCR) classified like of care and seriously non-ventilated patients with moderate hypoxemia were received 300 mL convalescent plasma treatment. Each donation was tested for antibody titersIgG class anti-SARS-CoV-2 by UMELISA. The transfused plasma units had an average antibody titer of 836.00 ± 617.155. The time interval between the onset of symptoms and transfusion was 9 days (7.20± 3). Before and after each transfusion, clinical and laboratory parameters were evaluated. RESULTS:At 24-hour after the plasma transfusion, oxygen partial pressure increased from medium value of 70.4 to 101.6 mm Hg, C-reactive protein and lactate dehydrogenase enzyme values decreased in 3 of 5 patients; however, the ferritin values increased in all the patients. Post-transfusion hospital discharge time was from 48 hours to 12 days and the SARS-CoV-2 PCR was negative between 3 and 5 days. No adverse transfusion reactions were reported. CONCLUSION:This report emphasis about the efficacy and security of convalescent plasma transfusion to care and seriously non-ventilated patients infected like a preventive therapy for severe respiratory distress for SARS-CoV-2 virus disease.